2018
DOI: 10.1111/jan.13828
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer‐specific anxiety and the resulting health‐related quality of life in couples

Abstract: Nurses can improve the HRQOL of people and their spouses by implementing activities that promote health and energy and reduce stress and by administering a mindfulness intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…The results of both APIMs revealed a remarkable partner effect for anxiety and FoP on the patients’ HRQoL, suggesting that the spouses’ anxiety and FoP were substantially associated with HRQoL of the patients with aPC. This result is in line with our hypothesis and the results of a previous study [ 9 ] suggesting that increased psychological burden in the spouses of patients with aPC might lead to less social support, which could lead to poorer HRQoL in patients with aPC. This hypothesis is supported by the results of a longitudinal study of patients with PC and their spouses that showed that spouses support and having the patients feeling supported significantly predicted the patients’ QoL and relationship satisfaction [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of both APIMs revealed a remarkable partner effect for anxiety and FoP on the patients’ HRQoL, suggesting that the spouses’ anxiety and FoP were substantially associated with HRQoL of the patients with aPC. This result is in line with our hypothesis and the results of a previous study [ 9 ] suggesting that increased psychological burden in the spouses of patients with aPC might lead to less social support, which could lead to poorer HRQoL in patients with aPC. This hypothesis is supported by the results of a longitudinal study of patients with PC and their spouses that showed that spouses support and having the patients feeling supported significantly predicted the patients’ QoL and relationship satisfaction [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of an APIM with cancer survivor dyads from the USA (21.5% PC) have shown that partners’ FoP was significantly associated with the mental and physical HRQoL of patients and partners, while the patients’ FoP showed no association with the partners’ HRQoL [ 22 ]. A similar pattern revealed by a longitudinal study with 48 Asian couples showing that spouses’ prostate-specific anxiety and self-reported health status contributed to the physical HRQoL (but not the mental HRQoL) of the patients with PC [ 9 ]. Another study investigated the association between depression and FoP in couples with PC and laryngeal cancer and showed that partners’ depression predicts patients’ and partners’ FoP.…”
Section: Purposesupporting
confidence: 69%
See 1 more Smart Citation
“…Being a spousal caregiver is associated with greater psychosocial and financial unmet needs and higher distress [ 76 , 77 ]. Spousal caregivers with higher marital satisfaction usually have better mental well-being when providing care to the patient [ 78 , 79 ]. However, an insecure attachment between spousal caregiver and patient may prevent them from using common dyadic coping, and result in impaired quality of life [ 80 ].…”
Section: Factors Influencing Informal Cancer Caregivingmentioning
confidence: 99%
“…Nonetheless, PCa presents the fifth‐highest male cancer incidence rate in Taiwan and it is the seventh leading cause of cancer deaths (Health Promotion Administration, Ministry of Health and Welfare, 2018). The diagnosis and treatment of cancer not only result in worsened psychological states, relationship satisfaction and health‐related quality of life (HRQOL) in patients with PCa but also affect their partners (Chien et al, 2017; Chien et al, 2019; Oba et al, 2017). Men who are newly diagnosed with PCa and their partners often experience psychological distress, anxiety and depression (Lehto et al, 2018; Oba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%